Censorship: News Media (Algeria) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Algeria. Data sourced from CensoredPlanet.
Censorship Incident ID: DZ-2024-0001. Severity: warning. Confidence: 75%